2016
DOI: 10.3389/fmicb.2016.01770
|View full text |Cite
|
Sign up to set email alerts
|

Different Flour Microbial Communities Drive to Sourdoughs Characterized by Diverse Bacterial Strains and Free Amino Acid Profiles

Abstract: This work aimed to investigate whether different microbial assemblies in flour may influence the microbiological and biochemical characteristics of traditional sourdough. To reach this purpose, members of lactic acid bacteria, enterobacteria, and yeasts were isolated from durum wheat flour. Secondly, the isolated microorganisms (Pediococcus pentosaceus, Saccharomyces cerevisiae, Pantoea agglomerans, and Escherichia hermannii) were inoculated in doughs prepared with irradiated flour (gamma rays at 10 kGy), so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 63 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Antifungal activity has been found in fermented doughs using selected M. guilliermondii strains [ 76 ]. However, S. cerevisiae was never isolated from the 20 types of flours prospected in this study ( Figure 1 d), although it was later isolated from HTC flours of tritordeum ( Figure 3 ); in fact, it was suggested that this species may have a flour origin [ 111 , 112 , 126 ]. S. cerevisiae was also isolated from tritordeum grains (GTit), a species not reported to be found in cereal grains.…”
Section: Discussionmentioning
confidence: 91%
“…Antifungal activity has been found in fermented doughs using selected M. guilliermondii strains [ 76 ]. However, S. cerevisiae was never isolated from the 20 types of flours prospected in this study ( Figure 1 d), although it was later isolated from HTC flours of tritordeum ( Figure 3 ); in fact, it was suggested that this species may have a flour origin [ 111 , 112 , 126 ]. S. cerevisiae was also isolated from tritordeum grains (GTit), a species not reported to be found in cereal grains.…”
Section: Discussionmentioning
confidence: 91%
“…One explanation for the yeast/LAB coexistence, even in the presence of negative interactions, is that yeasts and LAB are unintentionally reinoculated regularly in sourdoughs because they are present in the bakery house environment. Indeed, a strong effect of the house microbiota on sourdough microbiota has been already described [16,24,32,33]. Another nonexclusive explanation for the coexistence of yeast and LAB in sourdoughs is that the sourdough production process never leads to the exhaustion of fermentable carbohydrates, and therefore, competition for resources is weak.…”
Section: Discussionmentioning
confidence: 99%
“…When starters are made, the first microorganisms with the opportunity to colonize the starter are those in the flour itself. Flour has the potential to contain both species of microorganisms that lived inside the grain (endophytes) and those species found living on the outside of the grain or that colonize the grain during processing and storage (9). In theory, microorganisms in water could also colonize, but none of the common microorganisms in water systems are thought to play a major role in starters (13).…”
mentioning
confidence: 99%